Distributions of birds and plants in ecoregions: Implications for the conservation of a neotropical biodiversity hotspot. (22nd June 2018) - dos Anjos, Luiz; Volpato, Graziele H.; Lopes, Edson V.; Willrich, Guilherme; Bochio, Gabriela M.; Arakaki Lindsey, Barbara R.; Simões, Nadson R.; Mendonça, Luciana B.; Boçon, Roberto; Carvalho, Joema; Lima, Marcos R.
Abstract: The delineation of unique areas in biodiversity is crucial for conservation planning. However, identification of distinct biotas is a challenging task. In this study, we use an objective analytical process to test if bird and plant species composition of three different forest formation in the Atlantic forest Biome is sufficiently distinct to merit the recognition of ecoregions. We also evaluated how current climatic and spatial factors shape the distribution of plants and birds. Sampling localities were selected in three forest types of southern Brazil: mixed rain forest (MF), seasonal semi‐deciduous forest (SF) and dense rain forest (DF). The point‐centred quarter method and point counts were used to sample plants and birds respectively. Multivariate analyses were used to evaluate species composition, while the Rank Occupancy Abundance Profile was used to determine the association of bird species with each forest type. We used variation partitioning to determine which factors, that is climatic, spatial or tree species abundance (in the case of birds) better explained the distribution of plants and birds. A total of 176 tree species and 270 bird species were recorded. The bird species composition was sufficiently distinct among the three forest types, but the plant species composition was only distinct between DF and MF. Moreover, 61% of bird species were associated with only one forest type. This high association and the different species composition suggest that these forest types are sufficiently distinct to merit the recognition of ecoregions. Plant distribution was mainly affected by climatic variables, while bird distribution was mainly influenced by forest type and less so by climatic variables. Our data suggest that all three forest types should be conserved, but conservation strategies are urgent in MF where only 0.39% of its original cover is under protection.